La cueillette professionnelle de plantes sauvages, un travail vivant ? - Valentin Asselain (EchoGéo)
The wild plants professional foragers in mainland France form a diversified professional group. Foraging was formerly integrated within traditional peasantry, but contemporaneous foragers’ careers and discourses relate to neo-rural populations. Various professionalisation processes are being unfolded and claimed by the foragers. They carry their activity within the fringes of agriculture and in the natural spaces. Among other things, they aim at strengthening plants sustainability, improving their income or expecting herbal medicine to be better recognized. Despite their differences, they convey a particular relationship and a fresh look at work practices. It allows them to let sensitive, emotional or irrational dimensions flourish into their dynamic relation with the living. Hence, professional foraging embodies an interesting “living labour”, fuelling the criticism of the hegemonic organisation of work that is a source of multiple and widespread suffering.